Illustrated science and the fear of the divine: Speeches by Antonio Caballero y Góngora on the smallpox epidemic in the New Kingdom of Granada 1782-1783 - Quintero O., David (2021)
This article seeks to analyze the documentation produced between 1782 and 1783 by the archbishop-viceroy of the New Kingdom of Granada Antonio Caballero y Góngora, regarding the smallpox epidemic in this territory. From his pastoral letter issued in 1782 and his subsequent reports to the Indian minister José de Gálvez, it is possible to see the coexistence of two speeches in the face of the same event, on the one hand, the one that promoted the practice of inoculation as the remedy for face the disease, being the result of the advances of enlightened science and another, aimed at the general population where smallpox was presented as a divine punishment sent by God after the episode of infidelity that shook the viceroyalty. The union of both elements did not represent a contradiction, but on the contrary, it accounts for the mentality of a time where the weight of Catholicism and the impulse of the Enlightenment easily coexisted in the subjects.